The prevalence, influential factors and mechanisms of relative age effects in UK Rugby League - Till, K.; Cobley, S.; Wattie, N.; O'Hara, J.; Cooke, C.; Chapman, C. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Relative age effects (RAEs), reflecting observed inequalities in participation and attainment as a result of annual age-grouping policies in youth sport, are common in most team sports. The aims of this study were to determine if and when RAEs become apparent in Rugby League, determine how influential variables (e.g., gender) lead and clarify whether player retention at junior representative levels can explain persistent RAEs. Player data were collected for the male and female community games ranging from Under 7s to Senior (N=15 060) levels, junior representative selections (i.e., Regional) and professional players (N=298). Chi-square analyses found significant (P<0.05) uneven birth date distributions beginning at the earliest stages of the game and throughout into senior professionals. In junior representative selections, 47.0% of Regional and 55.7% of National representative players were born in Quartile 1, with RAE risk increasing with performance level. Gender and nationality were also found to moderate RAE risk. When tracking representative juniors, over 50% were retained for similar competition the following season. Findings clearly demonstrate that RAEs exist throughout Rugby League with early selection, performance level and retention processes, appearing to be key contributing factors responsible for RAE persistence.